Marriage Cancellation due to Force and Threats (Juridical Review of the Decision of the Religious Court of Tanjung Karang Regency Number 0174/Pdt.G/2020/PA.Tnk) - Kasmudin Harahap (IHSA Institute, 2022)
Arrangements for the annulment of marriages are regulated in Articles 22 to 28 of the Marriage Law. In the provisions of Article 22 it is stipulates that